Syphilis, history, science, and arts: syphilis history calendar - Passos, Mauro Romero Leal (2021)
Introduction: Syphilis is a very old disease involved by many mysteries. From its origins to the reason why even having simple and effective diagnosis and treatment for more than half a century, it remains, in 2021, as a public health problem practically all over the world. Be it in high-developing countries as well as in developing ones. Objective: To relate and describe, with dating, by day, month and year, in a calendar model, events and important characters that involve studies and quotes about syphilis. Methods: We used the prior personal knowledge of health professionals and researchers, who have worked in the field of sexually transmitted diseases for decades, combined with the search on the Internet, often on Wikipedia and Google, about events and characters involving subjects and publications about syphilis. Results: After several analyses and researches, we listed 68 facts and characters from around the world, including several Brazilians. Conclusion: At a time (2020 and 2021) where the subject, worldwide, on a daily basis, is SARS-CoV-2/COVID-19, this unprecedented publication on facts and characters involving syphilis can be a milestone so that, in addition to technical and scientific knowledge, the academic community realizes the anthropological, sociological, and cultural wealth that involves an entity that is much more than an infectious disease, such as syphilis.